Note from Campbell Morfit to Margaret M. Booth - Morfit, Campbell (1891)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes to Booth's widow, Margaret M. Booth née Cardeza, with his "best wishes for xmas and the new year."
Keywords: Morfit, Campbell, 1820-1897; Booth, James Curtis, 1810-1888; Martinez Cardeza, Margaret